2020
DOI: 10.3390/coatings10090866
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Color of Restorative Material Change during Exposure to Dietary Liquids Due to the Acquisition of a Discolored Layer?

Abstract: (1) Background: The aim of the paper is to determine how selected staining liquids affect color stability and reflectance of six composite and compomer dental materials. (2) Methods: Six dental materials were chosen for this study: G-aenial (GC), Filtek Z550 (3M), Herculite XRV Ultra (Kerr), Compoglass (Ivoclar Vivadent), Dyract Extra (Dentsply), and Dyract Flow (Dentsply). Ten staining liquids were used (distilled water, tea, tea with sugar, coffee, coffee with sugar, Coca-Cola®, orange and currant juices, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The absorption and adsorption of colourants with different polarities, found in different beverages, on the surface of resin composites have also been proposed as potential factors. Additionally, it has been suggested that silanisation of filler particles plays an important role in discolouration due to the fact that silane has high water absorption levels [4,8,9,11,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption and adsorption of colourants with different polarities, found in different beverages, on the surface of resin composites have also been proposed as potential factors. Additionally, it has been suggested that silanisation of filler particles plays an important role in discolouration due to the fact that silane has high water absorption levels [4,8,9,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described in the literature, the following scale was used to classify the resulting colour difference values (∆E): a difference below 2.0 units in the CIE colour space was classified as unnoticeable, between 2.1 and 3.5 units as slightly perceptible, between 3.6 and 5.0 units as clearly perceptible, and 5.1 units or above as pronounced [11].…”
Section: Colour Stability Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A change in color may also affect translucency, further altering the initial esthetics [16]. Discoloration of restored teeth over the long-term constitutes a reason for patient dissatisfaction, repeating the polishing procedure, or even restoration replacement [20][21][22]. The composition of the resin matrix, filler loading, and the composition and size of filler particles may also affect composite translucency [6,10,23].…”
Section: Introductionmentioning
confidence: 99%